2008
DOI: 10.1523/jneurosci.1857-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Derived from NOX1/NADPH Oxidase Enhance Inflammatory Pain

Abstract: The involvement of reactive oxygen species (ROS) in an augmented sensitivity to painful stimuli (hyperalgesia) during inflammation has been suggested, yet how and where ROS affect the pain signaling remain unknown. Here we report a novel role for the superoxidegenerating NADPH oxidase in the development of hyperalgesia. In mice lacking Nox1 (Nox1 Ϫ/Y ), a catalytic subunit of NADPH oxidase, thermal and mechanical hyperalgesia was significantly attenuated, whereas no change in nociceptive responses to heat or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 41 publications
2
124
0
1
Order By: Relevance
“…However, induction of Nox mRNA expression is observed in response to physical stimuli, (shear stress, pressure), growth factors (plateletderived growth factor, epidermal growth factor and transforming growth factor b), cytokines (tumor necrosis factor-a, interleukin-1 and platelet aggregation factor), mechanical forces (cyclic stretch, laminar and oscillatory shear stress), metabolic factors (hyperglycemia, hyperinsulinemia, free fatty acids, advanced glycation end products and G protein-coupled receptor agonists (serotonin, thrombin, bradykinin, endothelin and Ang II). [107][108][109] Nox enzymes are also regulated by ClC-3, Poldip2 and protein disulfide isomerase. Poldip2 associates with p22phox to activate Nox4, leading to regulation of focal adhesion turnover and vascular smooth muscle cell migration, thus linking ROS production and cytoskeletal remodeling.…”
Section: Vascular Generation Of Rosmentioning
confidence: 99%
“…However, induction of Nox mRNA expression is observed in response to physical stimuli, (shear stress, pressure), growth factors (plateletderived growth factor, epidermal growth factor and transforming growth factor b), cytokines (tumor necrosis factor-a, interleukin-1 and platelet aggregation factor), mechanical forces (cyclic stretch, laminar and oscillatory shear stress), metabolic factors (hyperglycemia, hyperinsulinemia, free fatty acids, advanced glycation end products and G protein-coupled receptor agonists (serotonin, thrombin, bradykinin, endothelin and Ang II). [107][108][109] Nox enzymes are also regulated by ClC-3, Poldip2 and protein disulfide isomerase. Poldip2 associates with p22phox to activate Nox4, leading to regulation of focal adhesion turnover and vascular smooth muscle cell migration, thus linking ROS production and cytoskeletal remodeling.…”
Section: Vascular Generation Of Rosmentioning
confidence: 99%
“…Intriguingly, phosphorylation of the RGS protein by various kinases including PKC has been documented to regulate GAP activity (Willars, 2006). In preceding communication, we reported that activation of PKC by ROS derived from NOX1 was the key mechanism underlying the development of hyperalgesia (Ibi et al, 2008). As a logical extension of these findings, a possible correlation may exist between NOX1/NADPH oxidase and desensitization of MOR.…”
Section: Introductionmentioning
confidence: 68%
“…؊/Y Previously, no difference in locomotor activity and coordinated movement was found between Nox1 ϩ/Y and Nox1 Ϫ/Y (Ibi et al, 2008). In untreated mice, no significant difference in the threshold for thermal (9.64 Ϯ 0.52 s latency in Nox1 ϩ/Y vs 8.43 Ϯ 0.34 s in Nox1 Ϫ/Y , N ϭ 9 -10) and mechanical (107.32 Ϯ 7.55 g in Nox1 ϩ/Y vs 99.30 Ϯ 6.45 g in Nox1 Ϫ/Y , N ϭ 10) nociceptive stimuli was observed between the two genotypes.…”
Section: Morphine-induced Analgesia Was Potentiated In Nox1mentioning
confidence: 93%
See 2 more Smart Citations